2019
DOI: 10.1111/corg.12270
|View full text |Cite
|
Sign up to set email alerts
|

Between politics and business: Boardroom decision making in state‐owned Indonesian enterprises

Abstract: Research Question/Issue: A significant part of the world's economy is controlled by state-owned enterprises, and there is a lack of research on how the interplay between politics and business plays out in the boardroom. We address this issue by analyzing boardrooms' decision outcomes as they relate to the role of boardroom power distribution, members' motivation, and decision-making approach.Research Findings/Insights: On the basis of information from a sample of 22 stateowned Indonesian enterprises, we found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 77 publications
1
22
0
Order By: Relevance
“…They find that board structure index is statistically significant when predicting Tobin's q in Brazil, and this result is driven mostly by board independence. As discussed earlier, board independence is highly relevant for SOEs, since members nominated by the government can be manipulated to achieve politi- cal interests seldom aligned with firms' business interests, and thus impacting their outcomes (Apriliyanti and Randøy;. Moreover, our results corroborate findings from other studies involving board attributes and firm value, also proxied by Tobin's q, such as Fauver et al (2017), Kao et al (2019) and Bhat et al (2018) for a sample of SOEs in Pakistan.…”
Section: Descriptive Statisticssupporting
confidence: 85%
See 2 more Smart Citations
“…They find that board structure index is statistically significant when predicting Tobin's q in Brazil, and this result is driven mostly by board independence. As discussed earlier, board independence is highly relevant for SOEs, since members nominated by the government can be manipulated to achieve politi- cal interests seldom aligned with firms' business interests, and thus impacting their outcomes (Apriliyanti and Randøy;. Moreover, our results corroborate findings from other studies involving board attributes and firm value, also proxied by Tobin's q, such as Fauver et al (2017), Kao et al (2019) and Bhat et al (2018) for a sample of SOEs in Pakistan.…”
Section: Descriptive Statisticssupporting
confidence: 85%
“…In this way, boards can be used as political tools, since they are unlikely to defy poor decisions made by political entities (Thompson et al;. Another conflict from the principal-principal perspective is that board members can be manipulated to support political interests that do not reflect the firms' business interests, therefore, impacting their performance (Apriliyanti and Randøy;.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies found positive effects of larger board size on the performance of firms. The ineffectiveness resulting from larger board are attributed to communication barrier when there are too many people involved in the decision-making process therefore, Apriliyanti and Randøy (2019) suggested that the number of BoD should be limited to ten (Apriliyanti and Randøy, 2019). Guest (2019) found out that smaller boards produce stringer returns, have stronger oversight, always more favorable (Guest, 2019).…”
Section: Board Size and Bank Financial Stabilitymentioning
confidence: 99%
“…The international scope of corporate governance research is indicated by the diverse set of governance environments studied in recent CGIR articles that include Australia, Canada, China, Germany, India, Indonesia, Iran, Italy, Japan, Korea, Russia, Spain, Sweden, Taiwan, the United Kingdom, the United States, and Vietnam, as well as multicountry studies (e.g., Deloof, Du, & Vanacker, 2020; Desender, LópezPuertas‐Lamy, Pattitoni, & Petracci, 2020; García‐Sánchez & García‐Meca, 2018; Lazzarini & Musacchio, 2018; Qian, Cao, & Cao, 2018; Tribó, 2019; Zhou & Guillén, 2019). Corporate governance research is by no means restricted to the average publicly held corporation but also deals with the unique challenges associated with specific types of firms like, for instance, audit firms (La Rosa, Caserio, & Bernini, 2019), banks (Sheedy & Griffin, 2018), business groups (Shin, Hyun, Oh, & Yang, 2018), closely held firms (Russino, Picone, & Dagnino, 2019), declining firms (Abebe & Tangpong, 2018), entrepreneurial ventures (Pérez‐Calero, Larrañeta, & Wright, 2019), family firms (Yeh & Liao, 2019), foundations (Thomsen, Poulsen, Børsting, & Kuhn, 2018), institutional investors (Semenova & Hassel, 2019), intergovernmental organizations (Federo & Saz‐Carranza, 2018), initial public offerings (IPOs) (González, Guzmán, Tellez‐Falla, & Trujillo, 2019), as well as state‐owned enterprises (Apriliyanti & Randøy, 2019). This research intensity demonstrates the spread of corporate governance studies in multiple disciplines but also leads to higher levels of fragmentation of the field.…”
Section: Introductionmentioning
confidence: 99%